Monitoring of the state of social and relations of the enterprise - Dragan, Olena; Maznyk, Liana (My University, 2020)
The innovative oriented society envisages the forming of new socially responsible labour relations. This range of problems is especially actual for the enterprises of food industry. The research is undertaken on the materials of Private Joint Stock Company “Monomakh” that runs tea business in Ukraine. Economic and mathematical methods are applied in the article: expert questioning, integral evaluation, taxonomical analysis. The object of the research is the process of social and labour relations state on Private Joint Stock “Monomakh”. Taking into account the specific of enterprises of food industry, there is the necessity of forming the monitoring system of social and labour relations state. The next component systems are following: normatively-legal providing, motivational providing, providing of normal terms of labour safety, organizationally staffing, sociocultural providing and development of personnel. For estimation of monitoring system efficiency of social and labour relations (SLR) state of the enterprise methodology that provides determinations single indexes, that characterize SLR; realization of ponderability estimation of monitoring system’s constituents of social and labour relations by the expert workers’ interviewing by Private Joint Stock Company “Monomakh” estimation of expert group coordination; determination of reviewer expert; the use of reviewer scale for calculation of integral index of SLR state; calculation of taxonomical index of SLR level; comparison of integral and taxonomical analysis results of SLR level are given. The taxonomy index of monitoring system of social and labour relations state is unstable. Beginning from 2016 had the tendency to the increase, and attained the maximum in 2017 ‒ 0,416, but in 2018 the index diminished ‒ 0,203, that testifies to the improper management of monitoring system of social and labour relations state on Private Joint Stock “Monomakh”. Precisely this conclusion was done on the results of integral evaluation. It is necessary to improve every indicator of influence separately for improvement of social and labour relations state, monitoring of which is effective exactly with application of corresponding taxonomical index and integral evaluation. The reasonable system of SLR state monitoring of the enterprise will allow to form a valuable InfoBase about existent areas of concern and work out events in relation to provide effective strategic development of SLR of the enterprise. Інноваційно орієнтоване суспільство передбачає формування нових соціально відповідальних трудових відносин. Цей спектр проблем особливо актуальний для підприємств харчової промисловості. Дослідження проведено за матеріалами Приватного акціонерного товариства «Мономах», яке веде чайний бізнес в Україні. У статті застосовано економіко-математичні методи: опитування експертів, інтегральне оцінювання, таксономічний аналіз. Об'єктом дослідження є процес соціально-трудових відносин держави на приватному акціонерному товаристві "Мономах". Враховуючи специфіку підприємств харчової промисловості, виникає необхідність формування системи моніторингу стану соціально-трудових відносин. Наступними компонентними системами є: нормативно-правове забезпечення, мотиваційне забезпечення, забезпечення нормальних умов безпеки праці, організаційне укомплектування персоналом, соціально-культурне забезпечення та розвиток персоналу. Для оцінки ефективності системи моніторингу соціально-трудових відносин (ЗСЗ) стану підприємства методологія, яка забезпечує визначення окремих показників, що характеризують ЗСЗ; проведення оцінки надійності складових соціально-трудових відносин системи моніторингу шляхом співбесіди експертів з приватною акціонерною компанією «Мономах» оцінки координації експертних груп; визначення експерта-рецензента; використання шкали рецензентів для розрахунку інтегрального індексу дзеркального стану; розрахунок таксономічного індексу рівня ЗБР; наведено порівняння результатів інтегрального та таксономічного аналізу. Індекс таксономії системи моніторингу стану соціально-трудових відносин нестабільний. Отже необхідно вдосконалювати кожен показник впливу окремо для поліпшення стану соціально-трудових відносин, моніторинг яких ефективний саме із застосуванням відповідного таксономічного індексу та інтегральної оцінки.
Keywords: кафедра економіки праці та менеджменту; social and labour relations state; monitoring system; enterprise; economic and mathematical methods; стан соціально-трудових відносин; система моніторингу; підприємство; економіко-математичні методи